Altered translational repression of an RNA‐binding protein, Elav by AOA2‐causative Senataxin mutation. Issue 5 (9th March 2017) - Choudhury, Saumitra Dey; VS, Ancy; Mushtaq, Zeeshan; Kumar, Vimlesh
Abstract: Mutations in Senataxin (SETX) gene causes two types of neurological disorders, Amyotrophic Lateral Sclerosis (ALS4) and Ataxia with Oculomotor Apraxia type 2 (AOA2). Recent studies in cultured cells suggest that SETX plays a crucial role at the interface of transcription and the DNA damage response. Whether SETX can alter translational of specific RNA is not known. In this study, we report that expressing AOA2‐causative truncated form of human SETX in Drosophila neurons alters the development of neuromuscular junction (NMJ) synapses. Interestingly, we found that expressing this truncated form of SETX in Drosophila muscles resulted in an alteration of translational repression of an RNA‐binding protein, Embryonic Lethal Abnormal Vision (Elav). Elav is transcribed in all tissues but remains translationally repressed except in neurons. Thus, our data suggest that an altered repression profile of RNA by SETX mutants could be one of the mechanisms underlying ALS4 or AOA2 pathogenesis. Abstract : Using Drosophila genetics combined with immunocytochemistry and confocal microscopy, we show that expression of AOA2‐causative pathological form of Senataxin alters translational repression of an RNAbinding protein, Elav. Thus, Senataxin may interact with translational machinery to regulate the cellular proteome.